Is Ozone therapy an adjunct treatment for SARS-CoV-2 / COVID-19 infection? - Pedro Iván Arias-Vázquez; Russell Arcila-Novelo; María Antonieta Ramírez-Wakamatzu (Universidade de São Paulo, 2022)
Abstract Up to today, there is no specific treatment against SARS-CoV-2 / COVID-19 infection; there the necessity to search for alternatives that help patients with COVID-19. The objective of this study was to review the use of ozone therapy as adjunct treatment for SARS-CoV-2 / COVID-19 infection, highlighting the mechanisms of action, forms of application and current clinical evidence. A systematic review was conducted in electronic databases, searching the terminology Ozone "or" Ozone therapy "and" SARS-CoV-2 or COVID-19 or Coronavirus. Results: nineteen studies were included; ten were editorials, comments, brief reports or reviews, and nine clinical studies. We found that ozone therapy could be favorable for treating patients infected with SARS-CoV-2 / COVID-19, through a direct antiviral effect, regulation of oxidative stress, immunomodulation and improvement of oxygen metabolism. Patients who were treated with ozone therapy responded favorably; therefore, ozone therapy appears to be a promising treatment for patients infected with SARS-CoV-2 / COVID-19. Its mechanism of action justifies its use as an adjuvant therapy; however, scientific evidence is based on case series and clinical trials are necessary to corroborate its effectiveness and safety.